2020
DOI: 10.1177/2632010x20970210
|View full text |Cite
|
Sign up to set email alerts
|

Ewing Sarcoma With Emphasis on Extra-skeletal Ewing Sarcoma: A Decade’s Experience From a Single Centre in India

Abstract: Introduction: The diagnosis of Ewing sarcoma family of tumours (ESFT) is challenging, especially in adults and in extra-skeletal or visceral location. Several morphologic mimics with varied treatment options and prognosis confer diagnostic dilemmas. Application of ancillary diagnostic modalities in surgical pathology in clinical routine has enabled accurate diagnosis of ESFT in bone, soft tissues, and viscera. Aim: The study aims to assess the clinicopathological features including molecular test results of ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…The immunohistochemical staining for S-100 protein, neurofilament protein, GFAP, desmin, F8, UEA-1, and keratin is negative. Finally, Ewing sarcoma can be diagnosed by detecting the rearrangement of EWS gene and related oncogene [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The immunohistochemical staining for S-100 protein, neurofilament protein, GFAP, desmin, F8, UEA-1, and keratin is negative. Finally, Ewing sarcoma can be diagnosed by detecting the rearrangement of EWS gene and related oncogene [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…ESFT of the cervix is rare and, to the best of our knowledge, only 28 cases were reported in the English literature between 1996 and 2020( Ahmad et al, 2017 , Hu et al, 2017 , Murthy et al, 2020 , Kyriazoglou et al, 2019 , Wang et al, 2017 ). We herein present a case of ESFT of the cervix and describe diagnostic and treatment procedures.…”
Section: Introductionmentioning
confidence: 97%
“…It accounts for 6%–8% of primary bone tumors in children and young adults, and its incidence peaks at 20, mostly in males 3 . Extra‐skeletal EWS/PNET is clinically rare with very low incidence, which accounts for about 1% of soft tissue sarcoma 2 . Primary pulmonary EWS/PNET (PPES) is extremely rare.…”
Section: Introductionmentioning
confidence: 99%
“…3 Extra-skeletal EWS/PNET is clinically rare with very low incidence, which accounts for about 1% of soft tissue sarcoma. 2 Primary pulmonary EWS/PNET (PPES) is extremely rare. Since Hammar et al reported the first case of PPES in 1989, 4 less than 40 cases have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation